Identification of a 45-kDa protein at the protein import site of the yeast mitochondrial inner membrane. - Scherer, P E (1992)
Import of proteins into mitochondria involves the cooperation of protein translocation systems in the outer and inner membranes. We have identified a 45-kDa protein at the protein import site of the yeast mitochondrial inner membrane. This 45-kDa protein could be crosslinked to a partly translocated precursor, which cannot be imported across the inner membrane when the matrix is depleted of ATP. In addition, an antibody against this protein strongly inhibited protein import into right-side-out inner-membrane vesicles. The 45-kDa protein accounts for only 0.1% of mitochondrial protein and appears peripherally attached to the outer face of the inner membrane. The properties of this protein suggest that it is a component of the protein import system of the mitochondrial inner membrane.